2020
DOI: 10.3389/fonc.2020.603480
|View full text |Cite
|
Sign up to set email alerts
|

HTRA3 Is a Prognostic Biomarker and Associated With Immune Infiltrates in Gastric Cancer

Abstract: HtrA serine peptidase 3 (HTRA3) participates in multiple signal pathways and plays an important regulatory role in various malignancies; however, its role on prognosis and immune infiltrates in gastric cancer (GC) remains unclear. The study investigated HTRA3 expression in tumor tissues and its association with immune infiltrates, and determined its prognostic roles in GC patients. Patients with GC were collected from the cancer genome atlas (TCGA). We compared the expression of HTRA3 in GC and normal gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…For example, CCL2, PRDM1, and LY6E were specifically highly expressed in immunomodulation1, and HTRA3 and PTGES were solely expressed in immunomodulation2 ( Figure 1F ). All these genes are involved in different immunomodulating processes based on previous studies ( Rafei et al, 2008 ; Fu et al, 2017 ; Wang T. et al, 2020 ; Ji et al, 2020 ; Pfaender et al, 2020 ) ( Figure 1E ). In line with this, we also observed overlapped features of immunomodulation and extracellular matrix-related GO terms in the two clusters, which are important for the maintenance of MSC functions ( Figure 1G ).…”
Section: Resultssupporting
confidence: 53%
“…For example, CCL2, PRDM1, and LY6E were specifically highly expressed in immunomodulation1, and HTRA3 and PTGES were solely expressed in immunomodulation2 ( Figure 1F ). All these genes are involved in different immunomodulating processes based on previous studies ( Rafei et al, 2008 ; Fu et al, 2017 ; Wang T. et al, 2020 ; Ji et al, 2020 ; Pfaender et al, 2020 ) ( Figure 1E ). In line with this, we also observed overlapped features of immunomodulation and extracellular matrix-related GO terms in the two clusters, which are important for the maintenance of MSC functions ( Figure 1G ).…”
Section: Resultssupporting
confidence: 53%
“…Early diagnosis of cancer is the key to improving the overall survival rate of patients, reducing disease-free progression, and reducing the risk of recurrence. Therefore, there is an urgent need to determine reliable predictive biomarkers and new therapeutic targets to truly improve the prognosis of patients.Studies have shown that abnormal gene expression is closely related to the occurrence and development of cancer [22,23].Nan Zhou's research shows that HTRA3 is abnormally highly expressed in gastric cancer tissues, and the high expression of HTRA3 indicates a poor prognosis [24].Liya Hu's research found that PDPN is a prognostic biomarker of gastric cancer and is related to immune in ltration [25].Li Rong's research con rmed that COL1A2 is a prognostic biomarker of gastric cancer through bioinformatics and Meta-analysis, which can improve the clinical predictive ability of gastric cancer [26].Therefore, it is very necessary to carry out bioinformatics research on gastric cancer. CHSY3 (Chondroitin Sulfate Synthase 3) is a Protein Coding gene,An important paralog of this gene is CHSY1.At present, the research on CHSY3 bioinformatics is relatively scarce.In our research, we mainly focus on the role of CHSY3 in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the survival association of these target genes because we wanted to obtain potential targets that affect survival. So far, TCGA data were widely used in prognostic studies [40][41][42]. The potential association of gene expression and overall survival might identify a biomarker for cancer prognosis or functional cancer regulator for cancer.…”
Section: Discussionmentioning
confidence: 99%